Pengaruh Pembelajaran Tatap Muka Terbatas Terhadap Kemandirian Anak - Stefani Corisa Putri; Ahmad Samawi; Nur Anisa (PG-PAUD Trunojoyo, 2023)
This research aims to describe and calculate the major effect of limited face-to-face learning in Kindergarten Kemala Bhayangkari 100 Malang. The research uses a quantitative approach with the type of correlational research with Spearman correlational analysis techniques through SPSS. The subjects studied were all children from Groups A and B with a side random sampling of 32 children, each class containing 8 children. Data collection using questionnaires, documentation, and interviews with teachers and parents. The results of the study show that the correlation coefficient is 0.571. This means that the effect of limited face-to-face learning on children's independence is strong. The hypothesis test shows that the t count is 3.78 greater than the ttable 2.750. From the results of the t-test showed that Ha was accepted while H0 was rejected. This means that there is a limited effect of face-to-face learning on children's independence in Kindergarten Kemala Bhayangkari 100 Malang which has a positive value. A higher level of face-to-face learning has a good influence on the high level of independence in children, as evidenced by the early admission of children there were 30 children in class B who could not wear their shoes, along with face-to-face learning at school with the efforts of teachers who provide various activities to train children's independence so that children are ready to continue to the higher education level.